Rate Regions of Two-Way Wireless Communication with Wireless Power Transfer under Different Factors - Zaino, Rami; Chuah, Teong-Chee; Hassan, Mohamed S. (International Conference on Electrical and Electronics Engineering, 2024)
This paper investigates the achievable rate regions of wirelessly powered two-way communication employing wireless power transfer (WPT) between two users, facilitated by either a fixed or a mobile relay. The analysis encompasses several factors, beginning with an examination of the impact of enabling energy harvesting on achievable rates with a fixed relay, considering diverse transmission distances and varying the number of relay antennas. The study also explores the unique scenario of direct communication between the two users. Additionally, the paper investigates the influence of mobile relay trajectories and velocity on the achievable rate region. Results demonstrate significant variations in achievable rates based on these factors. The findings offer valuable insights, paving the way for future research endeavors.